2016
DOI: 10.1121/1.4969375
|View full text |Cite
|
Sign up to set email alerts
|

Noise field characterization in the habitat of the East Taiwan Strait Indo-Pacific Humpback Dolphin during the pile driving activity of demonstration offshore wind farm

Abstract: The Eastern Taiwan Strait (ETS) population of Indo-Pacific humpback dolphin (Sousa chinensis) is listed critically endangered in the Red List of Threatened Species by the International Union for Conservation of Nature due to its small population size and narrow distribution. The humpback dolphin habitats off the coast of Miaoli and Changhua are sites selected for future wind farms, therefore, the noise impact of pile driving on this critically endangered population is expected to be serious. This paper present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These LCH waters should be protected immediately under the strictest disciplines. Activities inside the LHM that permanently alter the oceanographic and ecological features, such as a continuing wind farm project (Chen, Guan, et al, ), should be critically re‐evaluated and revised accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These LCH waters should be protected immediately under the strictest disciplines. Activities inside the LHM that permanently alter the oceanographic and ecological features, such as a continuing wind farm project (Chen, Guan, et al, ), should be critically re‐evaluated and revised accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The Indo‐Pacific humpback dolphin, Sousa chinensis , generally inhabits inshore (<20 m deep) waters in coastal and estuarine environments (Chen, Xu, et al, ; Jefferson, ; Jefferson & Hung, ; Jefferson & Karczmarski, ; Jutapruet et al, ; Jutapruet, Intongcome, Wang, Kittiwattanawong, & Huang, ; Wu, Jefferson, et al, ). Many humpback dolphin habitats are currently threatened by anthropogenic activities associated with coastal alterations (land reclamation, embankment, harbour construction, and aquaculture) (Chen, Huang, & Han, ; Jutapruet et al, ; Karczmarski et al, ; MacKinnon, Verkuil, & Murray, ; Wang, Wu, et al, ; Wu, Xu, et al, ), unregulated fishery activities (Jefferson & Smith, ; Slooten et al, ), pollutant accumulation (Gui et al, , ; Hung et al, ; Parsons, ), and underwater noises (Chen, Guan, et al, ; Pine, Wang, & Wang, ). Among these factors, recent studies have revealed that coastal alterations that immediately change the coastline geometry and substrate have altered the distribution of the humpback dolphin (Karczmarski et al, ; Wang, Wu, et al, ; Wu, Xu, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…1). These two turbines were the part of the Formosa 1 offshore windfarm project (Chen et al, 2017;Tseng, Lee, & Liao, 2017). Turbines were installed at a depth of ~35-55 m on a sandy substrate.…”
Section: Study Areamentioning
confidence: 99%
“…Turbines were installed at a depth of ~35-55 m on a sandy substrate. The two monopiles were 5.8 m in diameter and ~70 m in height (Chen et al, 2017). Geographical coordinates, pile driving start/end time, duration, and number of strikes are shown in Table 1.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation